Africa agriculture trade monitor 2021 - Bouёt, Antoine; Tadesse, Getaw; Zaki, Chahir (AKADEMIYA2063, 2021)
African countries have diversified both their exports and trade partners over the last decade, African agricultural trade still suffers from structural problems as well as exogenous shocks. Against this backdrop, the 2021 Africa Agriculture Trade Monitor (AATM) analyzes continental and regional trends in African agricultural trade flows and policies. The report finds that many African countries continue to enjoy the most success in global markets with cash crops and niche products. At the intra-African level, countries are becoming more interconnected in trade of key commodities, but there remain many potential but unexploited trade relationships. The report examines the livestock sector in detail, finding that despite its important role in Africa, the sector is concentrated in low value- added products that are informally traded. The report also examines trade integration in the Arab Maghreb Union (AMU), which remains limited due to factors including tariffs, nontariff measures, poor transport infrastructure, and weak institutions. Finally, the report discusses the implications of two major events affecting African trade in 2020 and 2021: the COVID-19 pandemic and the implementation of the African Continental Free Trade Area (AfCFTA).